Vocabulary Semantic Displacement and Development of Linguistic Performance - Alasaad, Khawla Mahmoud; Nawafleh, Mahmoud Rajaa (Journal of Arabic Language Sciences and Literature, 2022)
The study reveals the side of semantic displacement in language and shows vocabulary displacement to it. To achieve this, the study consisted of an introduction about the semantic displacement and its names since it is a linguistic phenomenon and a metaphor in order to emphasize and establish the meaning, and trace the deep meaning of displacement in the context and in the whole text, three themes: the first one was devoted to semantic change in the phenomenon of negativity or positivity and its reality is the opposite, tracing the deep effect to bring the semantic inspiration resulted from this certified constructed composition in choosing vocabulary in a special certain context. The second theme was displacement in the legal texts, tracing models from the holly Quran and showing the aesthetic of deep rhetoric usage to show inimitability of the holly Quran and distinguish its structures, and models of Sunna of the Prophet. The third theme was devoted to the internal and external factors of displacement, their discussion and giving models to explain them. Finally came the conclusion, result, margins list and sources and references list.
Keywords: Displacement; semantic; change; phenomenon; reality; metaphor